The Disruption of Retroperitoneal Interdigitating Dendritic Cell Sarcoma with Neurogenic Neoplasm as a Result of Immunohistochemical Markers and Radiological Features - Anil Pehlivan, Umur; Eren Erdogan, Kivilcim; Tugsan Balli, Huseyin; Erdogan, Seyda (Current Medical Imaging, 2023)
Introduction: Retroperitoneal localization is an extremely rare presentation of interdigitating dendritic cell sarcoma (IDCS), the primary neoplasm of the antigen-presenting interdigitating dendritic cells. Case Presentation: We report an incidentally found isolated retroperitoneal IDCS in a 59-year-old female patient with no prior symptoms. The patient was initially misdiagnosed since the tissue samples obtained by tru-cut biopsies were diffusely positive for S-100, and the radiological features were similar to neurogenic tumors. However, additional immunohistochemical staining in the excisional biopsy specimen revealed IDCS as the correct diagnosis. Conclusion: The correct diagnosis may not always be achieved with tru-cut biopsy evaluations in the retroperitoneal masses. Immunophenotyping and radiological features can occasionally be perplexing. In these cases, an accurate diagnosis can be achieved by excisional biopsy and additional immunohistochemical staining.
Keywords: Interdigitating dendritic cell sarcoma